2022
DOI: 10.1159/000524703
|View full text |Cite
|
Sign up to set email alerts
|

Typical Face, Developmental Delay, and Hearing Loss in a Patient with 3M Syndrome: The Co-Occurrence of Two Rare Conditions

Abstract: <b><i>Introduction:</i></b> 3M syndrome is an autosomal recessive disorder characterized by characteristic facial features, severe pre- and postnatal growth restriction (&#x3c;–4 SDS), and normal mental development. 3M syndrome is genetically heterogeneous. Up to date, causative mutations have been demonstrated in 3 genes, cullin-7 (<i>CUL7</i>), obscurin-like 1 (<i>OBSL1</i>), and coiled coil domain containing protein 8 (<i>CCDC8</i>). <b>&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Among these cases, 84 presented dual recessive diagnoses (AR + AR) and 22 presented multiple molecular diagnoses, with at least two recessive diagnoses (AR + AR + _). Furthermore, 72.64% (77 of 106) of these patients were known to be children of consanguineous parents [ 1 , 2 , 3 , 4 , 11 , 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. None of the reported cases carried recessive pathogenic variants simultaneously in the ASPM and CTNS genes, as the patient herein described.…”
Section: Resultsmentioning
confidence: 99%
“…Among these cases, 84 presented dual recessive diagnoses (AR + AR) and 22 presented multiple molecular diagnoses, with at least two recessive diagnoses (AR + AR + _). Furthermore, 72.64% (77 of 106) of these patients were known to be children of consanguineous parents [ 1 , 2 , 3 , 4 , 11 , 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. None of the reported cases carried recessive pathogenic variants simultaneously in the ASPM and CTNS genes, as the patient herein described.…”
Section: Resultsmentioning
confidence: 99%
“…Chinn et al reported an adult case with biallelic variations in ZAP70 and RNF168 having had a pediatric presentation ( 15 ). Another case report described developmental delay, and hearing loss in a patient with 3M syndrome due to co-existence variants in CUL7 and ILDR1 gene ( 16 ). Also, Amato et al reported a case of Angelman syndrome (5,5 Mb deletion of 15q11.2–q13.1) with a coexisting intermediate junctional epidermolysis bullosa (COL17A1, c.3766 + 1G > A, homozygous) and autosomal recessive deafness type 57 (PDZD7, c.883C > T, homozygous) ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chinn et al reported an adult case with biallelic variations in ZAP70 and RNF168 having had a pediatric presentation (15). Another case report described developmental delay, and hearing loss in a patient with 3M syndrome due to co-existence variants in CUL7 and ILDR1 gene (16). Also, Amato et al reported a case of Angelman syndrome (5,5 affiliated organizations, or those of the publisher, the editors and the reviewers.…”
Section: Discussionmentioning
confidence: 99%